Seismic-Hazard Maps for Alaska and the Aleutian Islands: PGA250 - Wesson, Robert L.; Frankel, Arthur D.; Mueller, Charles S.; Harmsen, Stephen C.; Rukstales, Kenneth S. (compiler) (USGS Science Data Catalog, 1999)
Probabilistic seismic hazard maps were prepared for Alaska portraying peak horizontal ground acceleration and horizontal spectral response acceleration for 0.2, 0.3, and 1.0 second periods with probabilities of exceedance of 10% in 50 years and 2% in 50 years. This particular data set is for peak horizontal acceleration with a 2% probability of exceedance in 50 years. All of the maps were prepared by combining hazard derived from spatially-smoothed historic seismicity with hazard from fault-specific sources. The acceleration values contoured are the random horizontal component. The reference site condition is firm rock, defined as having an average shear-wave velocity of 760 m/sec in the top 30 meters corresponding to the boundary between NEHRP site classes B and C. This data set represents the results of calculations of hazard curves for a grid of points with a spacing of 0.1 degrees in latitude and longitude. The grid of points were contoured to produce the final representation of the seismic-hazard.